Burns from ignited household aerosols in the kitchen: a case series - Anant Dinesh; Thais Polanco; Ryan Engdahl (SAGE Publishing, 2017)
Aerosol sprays are commonly used products in daily living. Aerosols in kitchen products have prompted for use of 'food grade' or chemically inert propellants; however, they commonly contain gases or gaseous mixtures such as butane, propane and dimethyl ether that are flammable. When such sprays are used near heat sources, such as kitchen appliances, combustibles in these products can result in ignition and burn injury. Given the ubiquity of such sprays, surprisingly burns sustained from household aerosols are not characterised in the literature. We conducted a retrospective search of all burn patients treated at our hospital which contains a burn unit. Three patients were identified with burn wounds due to household aerosol sprays. All three occurred in the kitchen. and were characterized as first-degree and second-degree burns over the head and neck or upper extremities with one requiring inpatient admission. Where it may be perceived a cause of minor injury, household aerosol burns may result in significant burn injury and hospital admission. Household aerosols and burn injury are reviewed.